Disruption of disruption innovation: a resource-based view (RBV) theory approach - Rizqi , Alfalahur; Indrian Supheni; Ambarwati , Ambarwati (Islamic Accounting Journal, 2024)
Objective & object: Disruptive innovation has become a key focus in modern business strategy because of its ability to revolutionize industries and create new market opportunities. Disclosure of disruptive innovation is a voluntary disclosure made by a company to provide information related to the company to stakeholders. This research aims to examine the influence of Human Capital, Structural Capital, and Relational Capital on the disclosure of disruptive innovation Methods: The population in this study was 33 companies, 132 samples, sampling used a purposive sampling method, and this research used a quantitative paradigm Results & Conclusions: The results of this research are that Human Capital, Structural Capital, and Relational Capital influence the Disclosure of Disruptive Innovation. However, it does not have a significant effect. Limitations: The weaknesses of this study are the absence of the Financial Services Authority (OJK) policy because this study refers to financial companies; and the lack of emphasis on concrete examples or case studies that support the application of the RBV concept in maintaining a company's competitive advantage. Using only one method of data collection can limit the depth and accuracy of the findings. Implications: The implications of this study for company management are expected to emphasize processing internal and external resources so that the company can become a company that has a sustainable competitive advantage. Investors need to evaluate the risks associated with the uncertainty of disruptive innovation and how companies manage these risks, especially if human, structural, and relational capital do not show significant influence. Keywords: Human Capital, Structural Capital, Relational Capital